Dendritic/Post-synaptic Tau and Early Pathology of Alzheimer’s Disease - Yin, Xiaomin; Zhao, Chenhao; Qiu, Yanyan; Zhou, Zheng; Bao, Junze; Qian, Wei (Frontiers in Molecular Neuroscience, 2021)
Microtubule-associated protein tau forms insoluble neurofibrillary tangles (NFTs), which is one of the major histopathological hallmarks of Alzheimer’s disease (AD). Many studies have demonstrated that tau causes early functional deficits prior to the formation of neurofibrillary aggregates. The redistribution of tau from axons to the somatodendritic compartment of neurons and dendritic spines causes synaptic impairment, and then leads to the loss of synaptic contacts that correlates better with cognitive deficits than amyloid-β (Aβ) aggregates do in AD patients. In this review, we discuss the underlying mechanisms by which tau is mislocalized to dendritic spines and contributes to synaptic dysfunction in AD. We also discuss the synergistic effects of tau and oligomeric forms of Aβ on promoting synaptic dysfunction in AD.